Improving Students' Ability to Read Hijaiyah Letters Through Picture And Picture Method in Grade 1 SD Negeri 07 Mandiangin - Rainelda, Rainelda; Dewi, Sinta; Hertati, Hertati (STKIP Rokania Pasir Pangaraian, 2024)
This study aims to improve the ability to read hijaiyah letters of grade 1 students of SD Negeri 07 Mandiangin through Picture and Picture method. This study used a classroom action research design (PTK) conducted in two cycles. The subjects of this study were 32 grade 1 students. Data were collected through observation, interviews, learning outcome tests, and documentation. The results showed that the Picture and Picture method can improve students' ability to read hijaiyah letters. In cycle I, the average student learning completeness reached 65.6%, while in cycle II it increased to 87.5%. The conclusion of this study is that the use of Picture and Picture method is effective in improving the ability to read hijaiyah letters of grade 1 students of SD Negeri 07 Mandiangin